2012
DOI: 10.1063/1.4750028
|View full text |Cite
|
Sign up to set email alerts
|

Hardness, yield strength, and plastic flow in thin film metallic-glass

Abstract: Lithiation-induced tensile stress and surface cracking in silicon thin film anode for rechargeable lithium battery J. Appl. Phys. 112, 093507 (2012) Mechanical and thermal behaviors of nitrogen-doped Zr-Cu-Al-Ag-Ta--An alternative class of thin film metallic glass Appl. Phys. Lett. 101, 181902 (2012) Effect of relative humidity on crack propagation in barrier films for flexible electronics J. Appl. Phys. 112, 083520 (2012) Torsion fracture of carbon nanocoils J. Appl. Phys. 112, 084311 (2012) Addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 31 publications
7
16
0
Order By: Relevance
“…Here the yield stress is defined to be the plastic flow stress at 1% offset strain. Note that this curve shows the same trend as in the pillar compression experiment [2,17].…”
Section: Cylinders Constrained By Base Materialssupporting
confidence: 66%
“…Here the yield stress is defined to be the plastic flow stress at 1% offset strain. Note that this curve shows the same trend as in the pillar compression experiment [2,17].…”
Section: Cylinders Constrained By Base Materialssupporting
confidence: 66%
“…To illustrate further connection with hardness, there are the two reports: first, by Akona, Reis and Ulm [401] on scatching materials ranging in hardness from butter to steel; and secondly, by Keryvin, Crosnier, Laniel, Hoang and Sangleboeuf [402] on scratching a ZrCuAlNi bulk metallic glass. The results of the latter report may be related to hardness and plastic flow measurements obtained on a related material by Ye, Chu, Chen, Wang and Yang [403].…”
Section: Thin Films and Coatingssupporting
confidence: 61%
“…26 For a shear band to nucleate and grow, a critical size scale, which is reported to range from ∼100 nm to 500 nm for Zr-based MGs, is required. 17,[27][28][29] Since our TFMG layer thicknesses are smaller than the critical shear-band nucleation size, shear bands do not develop, and TFMG plastic deformation is homogeneous. SAED patterns, including the one shown in the inset of Fig.…”
mentioning
confidence: 99%
“…7,[13][14][15][16] For example, 400-nm-thick Zr-based thin-film metallic glasses (TFMGs) in the form of micropillars were found to undergo homogeneous plastic flow with a dramatic plastic strain of 20% during microcompression tests. 17 However, the MG specimens used in all of these experiments were shaped by focused-ion-beam milling, which is known to result in ion damage during sample preparation. In recent years, Greer's group 18,19 reported that electrodeposited (FIB-free) nano-sized Ni-P alloy also exhibit good ductility.…”
mentioning
confidence: 99%